Reply to Comment on "Influence of Microwaves on the Water Surface Tension" - Parmar, H.; Asada, M.; Kanazawa, Y.; Asakuma, Y.; Phan, Chi; Pareek, V.; Evans, G. (2015)
In the comment on our publication “Influence of Microwaves on the Water Surface Tension”,(1) Amiri and Amiri commented on nonequilibrium conditions, fluid motion, and contamination from the Teflon during MW radiation. Here, we reply to the issues raised.